Two-wave study on intrapersonal stigma, social isolation, well-being, and functioning in individuals with chronic pain: A structural equation modeling approach - Van Alboom, M.; Bernardes, S. F.; Baert, F.; Bracke, P.; Goubert, L. (The Journal of Pain, 2025)
Stigmatization poses significant challenges for individuals living with chronic pain (CP), particularly when pain complaints lack a clear pathophysiological basis, referred to as primary CP. Although the negative impact of stigmatization on well-being and functioning of individuals with CP is acknowledged, its systematic and theory-driven investigations are sparse. Moreover, the underlying mechanisms linking CP stigmatization to adverse outcomes have yet to be examined. This study conducted an online, two-wave prospective questionnaire, collecting data from 332 individuals with chronic pain in the first wave (271 women, M age = 50y) and a subset of the same sample (N= 295; 241 women, M age = 54y) in the second wave (1 year later). Structural equation modeling revealed several key findings: (1) Individuals with primary CP perceived higher intrapersonal stigma compared to those with secondary CP. (2) Higher perceived stigma was related to increased mental distress and to decreased functioning/participation, both via higher levels of social isolation. 3) The structural relationships were not statistically equivalent across primary and secondary CP, suggesting moderation. 4) Finally, changes in perceived stigma were related to changes in functioning/participation in daily life and changes in mental distress, but only the model with mental distress was mediated by changes in social isolation. The findings underscore the importance of addressing perceived stigma and social isolation to improve mental health outcomes in CP patients. Clinically, tailored interventions that consider the unique needs of patients with primary versus secondary CP are necessary.